Cultural Landscape in Practice Conservation vs. Emergencies - Amoruso, Giuseppe; Salerno, Rossella (Lecture Notes in Civil Engineering, 2019)
This book approaches cultural landscape as a driver for societal challenges, economic development, social inclusion, place assessment and heritage conservation. It explores issues stemming from the relation between conservation and emergencies, and identifies descriptive tools for conveying knowledge and generating new expertise, heritage skills, seismic culture and social resilience. The documentation of landscapes, due in part to new technologies, increasingly involves integrated methodologies and graphic outcomes such as Heritage-BIM, advanced 3D modeling, and immersive environments. According to recent UNESCO recommendations, the process of mapping places is a necessary prerequisite for design action, and also includes the emotional and perceptive dimension, so as to represent space through visual thought and produce graphic materials. The chapters presented here will ultimately support efforts to overcome the emergency phase of reconstruction after natural disasters and, by exploring relevant issues in recent studies, will describe emerging tools that can help inspire practices that concern not only agrarian and urban, but also historic urban landscapes. The work also presents planning tools to help preserve the integrity and authenticity of urban heritages. The book will benefit all scholars and practitioners who are involved in the process of understanding, designing and transforming places, and will foster an international exchange of research, case studies, and best practices to confront the practical challenges involved in keeping cultural landscapes alive. .